(untitled) (Journal of Pharmaceutical Negative Results, 2019)
Objective: The objective of the study is to determine the effect of ethanolic extract of leaves of Solanum trilobatum (EEST) onscopolamine-induced memory impairment in Sprague Dawley (SD) rats. Materials and Methods: The leaves of S. trilobatum were extractedwith ethanol and used for the study. The SD rats were divided into six groups each consist of six animals, namely normal control; scopolaminecontrol; donepezil treated 3 mg/kg; and EEST treated 100, 200, and 400 mg/kg, respectively. Except normal control, all other animals wereadministered with intraperitoneal injection of scopolamine (1 mg/kg body weight) for 21 days to induce memory impairment. Donepezil andEEST were administered once daily through oral gavage for 21 consecutive days. On prestudy, 7th, 14th, and 21st days of the experiment, theanimals’locomotor activity, muscle grip strength and escape latency time (ELT) were measured. At the end of the study, blood samples werecollected from all the animals and they were sacrificed; the organs such as brain, liver, lung, heart, kidney, and stomach were harvested, andabsolute organ weight was measured. Blood samples were used for the biochemical analysis. Results: The rats treated with EEST 100, 200,and 400 mg/kg did notshow any change in locomotor activity and grip strength and significantly reduced motor resistance. The animalstreatedwith donepezil showed a significant reduction in ELT. The animals treated with EEST 100 and 200 mg/kg showed significant increases inELT, whereas animals treated with EEST 400 mg/kg did not show significant changes in ELT compared with that of prestudy. At the end ofthe study, EEST‑treated animals did not show significant changes in biochemical parameters, whereas donepezil‑treated animals showed asignificant increase in cholesterol level compared with control animals. Furthermore, EEST did not affect regular body weight gain, absoluteand relative organ weight. Conclusion: EEST did not show neuroprotective effect at lower doses in rats, but the high dose (400 mg/kg)prevented scopolamine‑induced memory impairment, and this effect is not significant when compared with standard donepezil.